Factors associated with the pollination of the cocoa (Theobroma cacao L.) crop - Ríos-Moyano, Diana Katherinne (2023)
Introduction. Pollination is important in many agricultural systems worldwide, including cocoa cultivation (Theobroma cacao L.) cultivation, which relies on insect activity for pollination. Objective. To compile the most 2021 and 2022, with an exhaustive search of literature related to cocoa crop pollination and pollinators in scientific articles, in Spanish, English, and Portuguese. Information was obtained from databases, university repositories, research journals, and digital agricultural libraries. The pollination of the cocoa crop is attributed to dipterans of the family Ceratopogonidae, specifically the genus Forcipomyia sp, which are more abundant during the rainy season. The presence of the insect has been associated with decomposing materials in the soil cover, due to its reproductive habits, making it important to provide moist shelters for the development of the pollinator larvae. Conclusions. Understanding cocoa pollination dynamics and the factors that affect it, is essential for conserving and increasing crop yields and farmers’ income worldwide. In cocoa cultivation, both biotic factors such as the presence of pollinators, clones used, and forest arrangements, and abiotic factors such as precipitation, temperature, radiation, and soil cover, play an initial role to consider in agricultural systems.